El deslizamiento del 8 de diciembre de 1994 en el volcán Irazú (Costa Rica): aspectos históricos y geomorfología con base en fotografías aéreas históricas y recientes - Fallas Solano, Mauro (2018)
On December 8th, 1994, at 22:48 (local time), a particular event took place on the northern flank of the Irazú volcano, which was described at that time as a phreatic eruption. Recently, the volcanic nature of this event was questioned and it was proposed that it would have been a debris avalanche generated by a landslide. In this work we studied this process from the historical, geological and geomorphological perspective. The hypothesis of the landslide is reinforced based on seismological evidences, although it is still not ruled out that geothermal activity could have been involved. In this work, the photogrammetric restitution was made from aerial photographs obtained by the National Geographic Institute (IGN) on December 20th, 1994, by which a volume of sliding material between 21±8 and 22±7x106 m3 was estimated.